2020
DOI: 10.1097/mca.0000000000000787
|View full text |Cite
|
Sign up to set email alerts
|

Reasons for early discontinuing or switching of antiplatelet therapy in elderly patients after acute coronary syndrome

Abstract: Objective This study aims to determine frequency and reasons for prematurely discontinuing or switching antiplatelet therapy in elderly patients admitted with non-ST-elevation acute coronary syndrome (NSTE-ACS). Method Patients of 75 years or older admitted with suspected NSTE-ACS were included between 2013 and 2016. Information was extracted from the patients’ medical files. Results A total of 544 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 14 publications
2
6
1
Order By: Relevance
“…However, after multivariate adjustment, this difference was not significant anymore. In agreement with our results, previous studies indicate PCI treatment as a predictor of DAPT adherence [6]. In our study, concomitant anticoagulant therapy was not an independent predictor of adherence (upper 95% CI boundary was 1.03), however the effect measure was heavily on the side of reduced adherence, in line with the findings in the ATLANTIS-SWITCH study [4].…”
Section: Fig 3 Kaplan-meier Curves Of Major Adverse Cardiovascular Ev...supporting
confidence: 92%
See 3 more Smart Citations
“…However, after multivariate adjustment, this difference was not significant anymore. In agreement with our results, previous studies indicate PCI treatment as a predictor of DAPT adherence [6]. In our study, concomitant anticoagulant therapy was not an independent predictor of adherence (upper 95% CI boundary was 1.03), however the effect measure was heavily on the side of reduced adherence, in line with the findings in the ATLANTIS-SWITCH study [4].…”
Section: Fig 3 Kaplan-meier Curves Of Major Adverse Cardiovascular Ev...supporting
confidence: 92%
“…Premature discontinuation of DAPT treatment during the first 12 months after the ACS event is not uncommon and has been so far linked to several factors. Current studies suggest that ticagrelor and prasugrel-treated patients are more prone to premature discontinuation than clopidogrel-treated patients [4][5][6]8,19,20]. In contrast, in the univariate analysis, patients treated with potent P2Y12 inhibitors as a form of DAPT were found to be more adherent than the patients treated with clopidogrel in our study.…”
Section: Fig 3 Kaplan-meier Curves Of Major Adverse Cardiovascular Ev...contrasting
confidence: 78%
See 2 more Smart Citations
“…However, several previous studies have reported that older patients receiving more potent P2Y12 inhibitors have a higher risk of bleeding ( 24 ) and even life-threatening bleeding (e.g., fatal intracranial bleeding) than younger patients, which leads to earlier mortality and reduced net clinical benefit. Additionally, premature discontinuation due to minor bleeding also places patients at a high risk for ischemic events ( 25 ).…”
Section: Discussionmentioning
confidence: 99%